MARRIAGE AND CUSTOMARY VIOLATIONS IN KAJANG COMMUNITY, BULUKUMBA REGENCY - Raodah, Raodah (Walasuji : Jurnal Sejarah dan Budaya, 2020)
This article is the research result conducted in Kajang community, Bulukumba Regency, which aims to describe and to analyze the customary violations in marriage that are not in accordance with the rule contained on pasang (message). If there is customary violation in a marriage, the violators will be subject to material and social sanctions in accordance with their violations occurred. This research applies a qualitative descriptive method, with data collection techniques through library study, interview, observation, and documentation. The result study shows that the forms of customary violations in marriage in Kajang community are silariang (eloping), nipitianangngi (pregnancy out of marriage), sexual harassment, and salimara (marriage with different social stratification). These customary violations in marriage are subject to customary sanctions of money and buffalo, while social sanction is nipassalai (excommunicated), either the pairs of marriage or their both family parties. The resolving rule of customary violations in marriage is carried out through customary deliberation attended by the traditional apparatus ammatoa, galla-galla, and the customary violators’ parties.